2008
DOI: 10.1021/jp8060224
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Enhancement of Sonoluminescence Activity by Altering Sonication and Solution Conditions

Abstract: An intensified charge-couped device (CCD) camera was used to capture raw images of multibubble sonoluminescence, generated by 168 and 448 kHz ultrasound. The effect of various air and surfactant concentrations, and pulse conditions on the acoustic pressure distribution, percentage of standing wave component, the structure of the sonoluminescence activity, and speed of streaming was investigated. It was observed that the enhancement in the sonoluminescence intensity by appropriate degassing, pulsing, and additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…It was reported that the decrease of dissolved gas concentration resulted in an increase in the threshold of acoustic pressure amplitude for rectified diffusion and a decrease in the coalescence of bubbles, which are the major pathways for the growth of bubbles in multibubble system . [27][28][29] Considering cavitation heat energy, it was observed that the increase of temperature by the ultrasound irradiation in the liquid was mainly due to sound absorption. The data presented in Table 1 shows that energy contribution by cavitation fluctuates significantly for the two frequencies and various liquid heights showing no predictable relationship.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the decrease of dissolved gas concentration resulted in an increase in the threshold of acoustic pressure amplitude for rectified diffusion and a decrease in the coalescence of bubbles, which are the major pathways for the growth of bubbles in multibubble system . [27][28][29] Considering cavitation heat energy, it was observed that the increase of temperature by the ultrasound irradiation in the liquid was mainly due to sound absorption. The data presented in Table 1 shows that energy contribution by cavitation fluctuates significantly for the two frequencies and various liquid heights showing no predictable relationship.…”
Section: Resultsmentioning
confidence: 99%
“…within the sonication cell. Lee et al [24,25] used high-speed and steady state imaging to monitor bubble clustering and cavitation activity. They have suggested that the spatial distribution of cavitation bubbles strongly depends upon various experimental conditions such as, dissolved gas and other solute concentrations, ultrasound frequency, pulsed sonication, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for not observing cavitation activity closer to the transducer region at higher frequencies is the moving of the cavitation bubbles by the travelling waves. Lee et al 18 have shown that the ratio between standing and travelling waves changes as a function of frequency, and travelling wave dominates at higher frequencies.…”
Section: Resultsmentioning
confidence: 99%